P722 Results of the STAR study: management of ulcerative colitis in private practice in france, in the first years following diagnosis. (25th January 2019) - Bourreille, A; Nancey, S; Attar, A; Sokol, H; Peyrin-Biroulet, L; Bouhnik, Y; Roblin, X; Bonnaud, G
Abstract: Background: The STAR study was conducted to describe the management of ulcerative colitis (UC) in private practices in France and to compare real-life data with European guidelines. Methods: STAR is an observational, retrospective, multicentre French study, conducted with private practice gastroenterologists. Data were collected in the medical records of patients, aged ≥18 years (yr), diagnosed with UC in the last 36 months (M) and followed-up for at least 12 M. Results: Ninety physicians included 249 patients, median age 36 yr, 48.7% women and 11.8% smokers. Median UC duration was 17.7 M. The Montreal classification of UC extent was E1 41.5%, E2 39.4% and E3 19.1%. Mean disease severity perceived by physicians (EVA 0–100 mm) was 35.07 at diagnosis and 19.00 at last visit. Mean Partial Mayo Score (PMS) was 4.20 at diagnosis and 2.02 at last visit. PMS at diagnosis was 58.2% mild, 25.8% moderate, and 11.1% severe. At last visit PMS was 51.1% remission, 37.1% mild, 7.4% moderate and 4.4% severe. The first endoscopy at diagnosis showed 38.3% light activity, 54.7% moderate and 5.5% severe activity. During the first yr of treatment (trt), 76.8% patients had no endoscopy, 9.1% had colonoscopy, 4.1% rectoscopy and 10% sigmoidoscopy. In the first yr of trt, endoscopies showed healing in 28.3% patients, mild activity 39.6%, moderate 26.4% and severe 5, 7%. Trt was 5-ASA in 97.9% patients, steroids 44.9%, immunosuppressants 20.3%, anti-TNF 18.2%. At last visit, 37.3% patients were no longer receiving 5-ASA. Oral 5-ASA was prescribed in 39.7% patients, rectal 27.5% and both 32.8% patients. 5-ASA was effective from first M in 79% patients. Mean dose oral 5-ASA induction trt was 3.60 g/day. Sixty-seven per cent patients had optimal mesalazine induction trt ( ≥4 g/day) and 13.1% had lower dose than European recommendations ( < 2.4 g/day). Mean oral 5-ASA maintenance dose was 2.14 g/day. Mean rectal induction dose mesalazine was 1.36 g/day. Median duration of oral induction trt was 83.5 vs. 48.5 d for rectal. 66.8% patients treated with 5-ASA first-line required no other drug class. 6.8% patients were hospitalised from diagnosis until the day of the visit. Since the diagnosis until the day of the last visit, 44.9% patients had steroids, 20.3% had immunosuppressants and 18.2% had at least one anti-TNF. Initiation of anti-TNF trt was not related to the severity of the disease at diagnosis (Mayo score 5). Conclusions: 5-ASA is the gold standard trt in UC induction and maintenance management and was effective from the first M of trt. 1/5 patients were treated with immunosuppressants and 1/5 with anti-TNF indicating that many patients went directly from 5-ASA to anti-TNF without exposition to immunosuppressants. The very high use of anti-TNF in mild-to-moderate UC could partly be explained by 5-ASA underdosing.